Prevalence of Abnormal Cervical Cytology in Pregnant Women and Its Associated Risk Factors - Kunwar , Radhika; Shakya, Beemba; Ansari , Shaheen Naaz (Journal of Bharatpur Hospital, 2025)
Background Cervical and breast cancer are the leading malignancies among females in Nepal. The World Health Organization (WHO) reported a crude cervical cancer incidence rate in Nepal of 14.2 per 100,000 women per year in 2022. Antenatal cervical screening provides an excellent opportunity to screen and create awareness for further surveillance. This study aimed to determine the prevalence of abnormal cervical cytology among pregnant Nepalese women and identify associated risk factors. Methods An observational cross-sectional study was conducted in Department of Obstetrics and Gynaecology at a tertiary center. Pregnant women between 20 and 28 weeks of gestation attending antenatal check-ups underwent liquid-based cytology (LBC). Cytology results were reported using the Bethesda classification system (2014). Results Among 78 enrolled pregnant women who completed the study, cytology indicated abnormalities in 58 women (74.4%), while 20(25.6%) were negative for intraepithelial lesion or malignancy (NILM). Among abnormal findings, inflammatory changes were most frequent 29(37.2%), followed by bacterial vaginosis 12(15.4%), Trichomonas vaginalis 12(15.4%), and candidiasis 5(6.4%). No premalignant or malignant lesions were detected. Conclusions Antenatal cervical screening offers a valuable opportunity to detect genital infections, screen for cervical cancer precursors, and raise awareness for future screening. Liquid based cytology test is easy to perform, cost effective and does not adversely affect pregnancy, playing a crucial role in reducing preventable cervical disease burden in low-resource settings.